A Study on the Feasibility of Utilizing the Metaverse Platform in Education - Na, Jiyoung (Digital Technologies Research and Applications, 2024)
As digital transformation accelerated after the COVID-19 pandemic, the use of metaverse has been increasing not only in the industry but also in the educational field. To adapt to the class site, it is necessary to derive a direction through foreign metaverse platforms. The following conclusions can be drawn from this study: First, it is difficult to express individuality through avatars, and non-verbal communication for conveying messages is challenging. Platforms like ZEPETO and ifland are in 3D, whereas Gather. The town is in 2D, and even then, the design is simplistic. Second, as the platforms are not specifically designed for educational purposes, there are limitations in supporting classes. Most are created for entertainment purposes. Third, most are one-time events. Particularly in the case of domestic Metaverse educational uses, the focus has been on one-time events rather than developing content that can be continuously used in classes. Fourth, most are one-time events. Particularly in the cases of domestic metaverse education cases, one-time events dominated rather than continuously available content in class. Fourth, when introducing metaverses into education, highlighting the purpose and benefits of using metaverse technology is crucial. Fifth, creating a user-friendly interface with a clear and simple menu is essential. Sixth, strong interactions between metaverse providers, suppliers, and users are essential. In this study, an analysis of the usage of metaverse in in the educational field and the direction of studying metaverse in this context in the future has been done. It is expected that the results of this study can be used as basic data in schools and development centers or development related to education content.